Flow resistance of individual neutrophils in coronary artery disease: decreased pore transit times in acute myocardial infarction. Issue 1 (January 1997) - Bauersachs, R. M.; Moessmer, G.; Koch, C.; Neumann, F. J.; Meiselman, H. J.; Pfafferott, C.
Abstract : OBJECTIVE: To investigate single neutrophil flow resistance in coronary artery disease, including myocardial infarction before initiation of reperfusion therapy. DESIGN: Neutrophil flow resistance was measured in 93 subjects in five groups: (group 1) 28 patients within 12 hours after the onset of myocardial infarction, before reperfusion therapy; (group 2) 18 with unstable angina; (group 3) 13 with stable angina; (group 4) 13 age matched patients without coronary disease, and (group 5) 21 healthy volunteers. MAIN PARAMETERS: Single neutrophil transit times through 8 microns oligopore filters determined with a modified cell transit analyser. RESULTS: Leucocyte count (10(9)/l) was increased in coronary disease, especially in myocardial infarction and unstable angina (mean and 95% confidence intervals for groups 1 to 5: 12.6 (11.0 to 14.2), 11.3 (8.5 to 14.1), 8.5 (7.4 to 9.6), 8.0 (6.0 to 10.0), 7.0 (6.1 to 7.9)). Polymorphonuclear granulocyte (PMN) flow resistance correlated negatively with white blood cell (WBC) count and was significantly decreased in coronary artery disease (CAD), especially in myocardial infarction; mean transit times (ms) for groups 1 to 5 were: 13.6 (11.8 to 15.4), 16.9 (13.9 to 19.0), 16.9 (12.8 to 21.0), 22.0 (19.6 to 24.4), and 18.6 (15.7 to 21.5). CONCLUSION: Neutrophil flow resistance was decreased in CAD, especially in myocardial infarction before reperfusion therapy. In contrast to previous findings in reperfused myocardial infarction, the present study showed that stiffened PMNs were not yet present in the circulating blood pool. Thus a pharmacological approach aimed at suppressing leucocyte activation before or during reperfusion therapy may be feasible.